Opportunities For Implementing Shariah-Based Green Finance in State-Owned Enterprises: a Case Study of Perum LKBN Antara in Supporting Sustainable Development Goals - Ernawati, Ernawati; Adiningsih, Tutut (LP2M IAIN Palopo, 2025)
This study aims to analyze the opportunities and challenges of implementing Sharia-based green finance in State-Owned Enterprises (SOEs), using Perum LKBN Antara as a case study. Sharia-based green finance is an innovative approach that integrates sustainability principles with Islamic values in the financial system. Using a qualitative method with a case study approach, data were collected through in-depth interviews, company documents, and annual reports, which were analyzed using NVivo software. The results show that Perum LKBN Antara has significant potential to adopt Sharia-based green finance, supported by internal awareness, environmentally friendly strategic policies, and ESG reporting practices. However, the implementation still faces several challenges, such as limited human resources, the absence of a structured sustainability roadmap, and a lack of understanding of Sharia principles in the context of green finance. This research recommends strengthening internal literacy, collaborating with Sharia-compliant institutions, and developing a roadmap and sustainability report based on Sharia ESG principles. This study is expected to provide both theoretical and practical contributions to the development of Sharia-based green finance in the public sector as a support for achieving the Sustainable Development Goals (SDGs). Keywords: Green Finance, Sharia Accounting, State-Owned Enterprises (SOEs), LKBN Antara, ESG, SDGs.